A fuzzy AHP model to assess sustainable performance of the construction industry from urban regeneration perspective - Işik, Zeynep; Aladağ, Hande (Journal of Civil Engineering and Management, 2017)
The construction industry needs to assess its performance in the long term, considering the intangible parameters together with the tangible ones. Urban regeneration as well as infrastructural development have considerable impacts on the construction industry performance in developing countries. Therefore, in order to provide efficient and sustainable performance for the construction industry in the long term, it is crucial to determine the benchmarks and indicators from the perspective of those projects. In this context, major objective of this study is to represent a model showing the parameters affecting the sustainable performance of construction industry from urban regeneration perspective. Fuzzy Analytic Hierarchy Process (FAHP) analysis was employed in order to determine measures and indicators associated with sustainable performance and a model was established reaching the objective of the study. According to the FAHP analysis results, among measures such as Company Performance, Extrinsic, Economic, Environmental, Social and Innovational Factors set in the research, intangible values such as innovation and social protection were also found to have prior effects as well as the inevitable tangible ones such as cost, profitability and macro economy to sustain the performance of the construction industry for urban regeneration projects in the long term. First published online: 03 Dec 2016